The influence of perceived information quality on travel satisfaction in Kuala Lumpur: a perspective of generational difference - Mohd, Nur Shuhadah; Najimudin, Muhammad Fadhlullah (Springer Nature Switzerland AG, 2024)
The surge in technology-mediated information systems has accentuated the need for dependable and functional information, particularly among Generation Y, addressing the intricate psychological needs of travellers. While the integration of technology in disseminating information may not assure enhanced quality, it’s anticipated to offer added value through its dynamic and interactive elements. Past studies have primarily focused on technology’s role in facilitating information distribution, with scant emphasis on the information quality sourced from this medium and its consequent impact on travel satisfaction. This research, therefore, delves into the influence of perceived information quality on travel satisfaction, focusing on mobile platform services. Using a quantitative approach, 288 responses were gathered from structured surveys in the urban tourism locale of Kuala Lumpur. The research employed Multiple Hierarchical Linear Regression Analysis to decipher the association between perceived information quality and travel satisfaction based on generational difference. Results shown that age disparities didn’t seem to affect relationship the way user perceived information and travel satisfaction. This study is expected to contribute in the enhancement of online information quality, urging information providers to judiciously evaluate criteria for premium information.